Enhancing Chitosan-Carboxymethyl Chitosan Composite Film Properties by Silver Nanoparticles Grafting for Acne vulgaris - Dwi Mulyana, Septian; Agus Syamsur Rijal, Muh.; Sari, Retno (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Silver nanoparticles (AgNPs) have been widely used in developing antibacterial preparations. AgNPs are used in film preparation to enhance the film’s antibacterial properties. The combination of natural polymers is an effective strategy to enhance mechanical properties, prolong degradation time, preserve gas and vapor permeability, and maintain biocompatibility. This research aims to develop an AgNP-chitosan-carboxymethyl chitosan (CMChi) nanocomposite film that exhibits desirable physical properties and enhances antibacterial activity by incorporating AgNPs. Chitosan-CMChi composite films were prepared using the solvent casting method. Characterization and antibacterial tests using Propionibacterium acnes (P. acnes) were carried out for AgNO3 and AgNP-chitosan-CMChi nanocomposite films. The results showed that a 1 mM AgNO3 solution with 1% lime powder at pH 9 was the optimal formulation for AgNP formation, exhibiting an absorbance of 4.631 at 408.1 nm, a particle size of 68.4 nm, and antibacterial activity. To optimize the chitosan-CMChi composite film, a formula of 1.5% chitosan and 1.5% CMChi was selected, yielding a tensile strength value of 0.514 MPa. The AgNP solution was then added. In the AgNP-chitosan-CMChi nanocomposite film, it was observed that increasing the AgNP volume affected the mechanical strength of the film. The antibacterial activity of the AgNP-chitosan-CMChi nanocomposite film increased with the AgNP concentration. Combining AgNPs with the chitosan-CMChi polymer yields nanocomposite films with good physical properties and enhanced antibacterial activity against P. acnes compared with films without AgNPs.